Kemampuan Penggunaan Kata Negasi 不 (bù) dan 没 (méi) dalam Kalimat Bahasa Mandarin Siswa Kelas VIII SMP FRATER Makassar. - Khafifa Fuji Lestari; Syukur Saud; Misnawaty Usman (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2022)
This research is a quantitative descriptive study that aims to obtain data on the ability to use the negation word 不 (Bù) and 没 (Méi) in Mandarin sentence of class VIII students of Makassar FRATER Middle School. The population in this study was students at class VIII of SMP FRATER Makassar consisting of 8 classes totaling 208 students. The sampling technique was carried out using random sampling, then the sample of this study was class VIII D which 30 students. This research data was obtained from the correct test true and false. Data is analyzed using a percentage technique with a 73%. The results showed that the level of ability to use the negation word 不 (Bù) and 没 (Méi) in the Mandarin sentence of students was in a capable category (73%). Keywords: Negritecting, 不 (Bù), 没 (Méi), Mandarin language.